2006
DOI: 10.1021/jp0601419
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Chloride as a Solid Is Not a Strong Lewis Acid

Abstract: Aluminum chloride is used extensively as Lewis acid catalyst in a variety of industrial processes, including Friedel-Crafts and Cl/F exchange reactions. There is a common misconception that pure AlCl3 is itself a Lewis acid. In the current study, we use experimental and computational methods to investigate the surface structure and catalytic properties of solid AlCl3. The catalytic activity of AlCl3 for two halide isomerization reactions is studied and compared with different AlF3 phases. It is shown that pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 22 publications
4
43
0
Order By: Relevance
“…AlCl 3 is a strong Lewis acid in the molecular state, but the solid itself possesses no or only very low acidity [82] (see also discussion in Section 4.3). From the point of view today many older results are doubtable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AlCl 3 is a strong Lewis acid in the molecular state, but the solid itself possesses no or only very low acidity [82] (see also discussion in Section 4.3). From the point of view today many older results are doubtable.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown recently by experimental and theoretical methods, that the (0 0 1) surface of solid AlCl 3 has no Lewis acidic centres [82], and is very similar to the catalytically inactive a-AlF 3 . All aluminium ions at the surface are coordinated by six chloride ions (Fig.…”
Section: Lewis Acidity Of Solid Aluminium Fluoride and Chloridementioning
confidence: 97%
“…In contrast, HS-AlF 3 was immediately active both in liquid as in gas phase reactions. Computational investigations showed that in the regularly ordered AlCl 3 all Al atoms next to the surface are completely covered and efficiently blocked by Cl atoms, in contrast to the highly disordered HS-AlF 3 [37].…”
Section: Examples Of Binary Metal Fluoridesmentioning
confidence: 97%
“…(8)) [25] and isomerisation of CCl 2 FCClF 2 (Eq. (9)) [37] and of CBrF 2 CBrFCF 3 (Eq. (10)) [21] used.…”
Section: Examples Of Binary Metal Fluoridesmentioning
confidence: 99%
See 1 more Smart Citation